Effect of dentin pretreatment on the resulting abrasive dentin wear - Blend Hamza; Marina Kazimi; Philipp Körner; Thomas Attin; Florian Just Wegehaupt (BMC, 2021)
Abstract Background This study aims to investigate the influence of different dentin pretreatment procedures on the resulting abrasive dentin wear. Methods Two groups (A, B) of 60 dentin samples each were prepared. Group A was brushed with an abrasive slurry (RDA = 85) and group B with a different abrasive slurry (RDA = 174). Four subgroups in each group (n = 15) were created (A1-A4) and (B1-B4). The subgroups were pretreated as follows: A1 + B1 with 1200-grit grinding paper, A2 + B2 with 1200- and 2000-grit papers, A3 + B3 with 1200-, 2000-, and 4000-grit papers, A4 + B4 with 1200-, 2000-, 4000-grit papers and with 1000 brushing strokes with a slurry of Elmex toothpaste. All samples were brushed for 25 min at 120 strokes/min. Abrasive dentin wear was measured for each sample profilometrically and the subgroups were compared with each other within the same group. Repeated measures one-way ANOVA was conducted to compare the subgroups and pairwise contrasts were estimated for multiple testing according to Tukey (α = 0.05). Results The resulting abrasive dentin wear in group A ranged between 15.3 ± 3.4 µm and 17.3 ± 5.5 µm and between 20.3 ± 6.8 µm and 22.5 ± 2.6 µm in group B. No statistically significant difference was noticed between any subgroups within the same group (p ˃ 0.05). Conclusions Different dentin pretreatment procedures do not affect the resulting abrasive dentin wear independent of the RDA value of the employed abrasive slurry.